A study on the chemical composition of Salicornia europaea L. found in the coastal area opposite the Jableh Corniche on the Syrian coast - Shakohi et al. (Iraqi Journal of Aquaculture, 2025)
The coastal area opposite Jableh Corniche was used to collect the leaves of Salicornia europaea L. in the winter of 2023. The organic extract was identified by performing analysis using gas chromatography-mass spectrometry (GC/MS) and high-performance liquid chromatography (HPLC) after extracting the leaves using a Soxhlet apparatus. The results showed the presence of 23 chemical compounds, accounting for 21.92% of the total organic extract of S. europaea L. leaves identified by GC/MS, and a percentage of 4.83% in the organic extract of S. europaea L. leaves identified by HPLC. The organic extract of S. europaea L. leaves showed five major compounds, listed in order: Palmitinic acid, oleic acid, phenol 2,4-bis(1,1-dimethylethyl), ω-3 linolenic acid, and stearic acid, with respective percentages of (16.6-13.48-12.7-9.13-6.71). Additionally, the identities of 11 phenolic and flavonoid compounds were determined, which constituted 4.83% of the organic extract of S. europaea L. leaves. The highest percentage was for chlorogenic acid with 3.6%, followed by eugenol with 1.1%. Consequently, the presence of diverse bioactive secondary metabolites and a large number of compounds gives a significant pharmaceutical importance to the studied plant.